2019
DOI: 10.1038/s41366-019-0357-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous rare genetic variants in non-syndromic early-onset obesity

Abstract: Background Obesity is a very heterogeneous disorder at both the clinical and molecular levels and with high heritability. Several monogenic forms and genes with strong effects have been identified for non-syndromic severe obesity. Novel therapeutic interventions are in development for some genetic forms, emphasizing the importance of determining genetic contributions. Objective We aimed to define the contribution of rare single-nucleotide genetic variants (RSVs) in candidate genes to nonsyndromic severe early-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 65 publications
(85 reference statements)
4
27
0
1
Order By: Relevance
“…The prevalence of pathogenic variants in MC4R in our cohort was 2% (2/92), which is comparable to previous reports (7,(10)(11)(12)(13)(14). The patients in our study with the novel MC4R frameshift deletion had severe childhood obesity and hyperphagia.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The prevalence of pathogenic variants in MC4R in our cohort was 2% (2/92), which is comparable to previous reports (7,(10)(11)(12)(13)(14). The patients in our study with the novel MC4R frameshift deletion had severe childhood obesity and hyperphagia.…”
Section: Discussionsupporting
confidence: 87%
“…We and others have also shown that rare copy number variants (CNVs) are enriched in patients with early-onset severe obesity (4)(5)(6). Recently, it has also been suggested that obesity could be a consequence of rare genetic variants with strong effect (7,8). Despite these advancements, the genetic causes and underlying molecular mechanisms behind obesity are still inadequately understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To exclude secondary causes of obesity in the study cohort, every patient's clinical record was reviewed, and the patients underwent a full obesity-oriented clinical examination by the same physician in all cases and complementary tests to rule out underlying pathologies (including thyroid function and cortisol production assessment) were performed. Additionally, no patient was found to exhibit pathologic findings in analysis by MS-MLPA for the detection of imprinting disorders, studies of CNVs (copy number variant) or in the sequencing of a panel of 15 obesity candidate genes ( 26 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…In heterozygous subjects, phenotypic expression may depend in part on the environment and the influence of other genes. These forms of obesity account for at least 5% of the causes of early and severe obesity (19), but this prevalence is probably underestimated and may be higher in certain populations, especially those in which consanguinity is frequently observed (16,20,21). Patients with compound heterozygous or homozygous variants for the LEP, LEPR, POMC, PCSK1, and MC4R genes show early severe obesity accompanied by impaired hunger and satiety signals (22,23,24,25,26,27,28).…”
Section: Clinical Subtypes Of Genetic Obesitymentioning
confidence: 99%